IMF Survey : Volume 28, Issue 07. (IMF Survey; IMF Survey ;, 1999)
IMF Managing Director Michel Camdessus visited Moscow from March 27 to March 29 and met with Russian Prime Minister Yevgeny Primakov and other senior officials. On March 29, Camdessus and Primakov issued a joint communique, the text of which follows.